Study of religion: The queen of study in humanities - Ibrahim, Haslina (Common Ground Publisher, 2008)
Man and religion are among the subjects of interest that configure the establishment of human intellectual tradition. However, tracing down the history of both areas, we are presented with multiple responses either in support of or against the subjects. The relation between the two is also another interesting area to embark on. In the case when the relationship is negatively perceived, it resulted into total separation between the two. In contradiction, when the two is perceived as exist in harmony, reconciliation between the two takes place. Unfortunately, the latter had not been the favorite choice. Tracing down the human history in general, we may be surprised that the relationship between man and religion had underwent severe conflict that lead to their divorce. The complete separation took place during modernity as man was enlightened by his own reasoning. Even religion falls under the domain of his reasoning. Study on humanities became the ‘lonely king’. Thus, religion being marginalized and privatized made a perfect ingredient for nurturing exclusivism and isolationism. We are now leaving in the post-modern time eating the bitter fruit of the divorce between the two which come under the disguise of nationalism, ethnocentricism and religious exclusivism. It is due to these challenges that this paper seeks to re-accentuate the study of religions as ‘the queen’ of the study in humanities without which the understanding of man fall short. On top of that, the paper attempts at highlighting the positive role the study of religions had for treating the current crisis in human relation.